Managing Migration: The Promise of Cooperation - Martin, Susan F.; Martin, Philip L.; Weil, Patrick (Lexington Books, 2006)
A growing share of the world's population lives in the 175 developing countries, while global income and wealth are increasingly concentrated in the 25 developed countries. The resulting migration from developing to developed countries is proving difficult to manage at national, regional, and local levels. Managing Migration presents the valuable results of the Cooperative Efforts to Manage Emigration project, a bottom-up effort to identify models and best practices for spurring economic development and respect for human rights in migrant countries of origin. Based on the research of experts from North America and Europe, authors Martin, Martin, and Weil discuss the challenges of managing international migration in the 21st century, present case studies in cooperative migration management, and offer recommendations to overcome the existing challenges. Concluding that there is no one-size-fits-all framework for managing migration, but that there are common elements of best-practice migration, Managing Migration is guaranteed to pique the interest of policy makers and practitioners involved in immigration as well as scholars of geography, anthropology, and international relations.